SISTEM INFORMASI PENJUALAN HIJAB PADA HAYYA HIJAB MENGGUNAKAN METODE AGILE SOFTWARE DEVELOPMENT - Fatjriah, Nur; Nur Sholihaningtias, Dian; Heriyati, Heriyati (PROFITABILITAS, 2023)
The aim of the research is to develop an existing hijab sales information system to make it easier to collect data and store data at Hayya Hijab. The research methodology used in the data processing system is the literature study method, namely data collection which is carried out by taking data from various online books, journals and other books that can be used as a basis for analyzing problems that can be discussed in research, as well as field study methods. namely by making direct observations such as interviews and observations. The system development method used is the Agile Software Development method. The result of this research is that there is an application tool made with the Java programming language and storing data using a database from MySQL so that the data collection process at Hayya Hijab becomes more effective, efficient and practical.